Legal Analysis of the Legal Protection of Patients Participating in New Drug Clinical Trials - E.Nasution; F.Alamsyah (The Medical Journal of Hospital Management and Health Law, 2026)
Introduction: The rapid development of pharmaceutical biotechnology necessitates clinical trials on human subjects to ensure drug safety and efficacy, yet this process inherently exposes patient-participants to severe health risks and potential exploitation. This study examines the adequacy of current legal frameworks in safeguarding human subjects during clinical trials of new investigational drugs. Methods: This study employs a normative juridical research method, analyzing primary, secondary, and tertiary legal materials, including international guidelines, national healthcare statutes, and consumer protection regulations. Results: The analysis reveals that while basic regulatory frameworks exist, significant legal vacuums remain regarding strict liability for clinical trial injuries, the enforceability of informed consent under asymmetric medical relationships, and comprehensive institutional oversight mechanisms. Discussion: The discussion comprehensively integrates a literature review regarding patient autonomy, bioethics, and state responsibility, highlighting how the unequal bargaining power between pharmaceutical sponsors and vulnerable patients undermines genuine consent. It evaluates the legal nature of clinical trial agreements, identifying them as adhesion contracts that require intervention through mandatory indemnification clauses and enhanced Institutional Review Board oversight. Conclusions: Current legal protections are fragmented and insufficient to address the complexities of modern clinical trials, necessitating a shift toward robust statutory strict liability and standardized operational protocols. It is recommended that the legislature enact a dedicated statute governing clinical trials and that healthcare authorities establish a mandatory state-backed insurance scheme to provide immediate compensation for injured participants without the burden of proving negligence.